Hubungan Kekuatan Otot Dengan Tingkat Kemandirian Activity Daily Life (ADL) Pasien Stroke di RSUD Dr. Loekmono Hadi Kudus - Ellena Virgin Cindy Puspita; Sri Puguh Kristiyawati; Novi Heri Yono (STIKes Ibnu Sina Ajibarang, 2024)
Stroke is a neurological conditions that causes blockage of rupture of blood vessels in the brain. It occurs suddenly and lasts for more than 24 hours. The condition causes the inability of stroke patients to fullfill daily activities. Stroke patients who experience a decrease in daily activity will cause their level of independence to decrease. The aim of the research was to determine the relationship between muscle strenght and the level of indepence in Activity daily life (ADL) of stroke patients at dr.Loekmono Hadi Kudus. This Reseach design uses correlation analytical method with a cross sectional design. The total sample for this research was 65 respondents using purposive sampling date collection techniques. The measuring tool used is the Katz Index. The statistical test obtained a p-value of 0.000 for each, so that Ha was accepted, which means there is a significant relationship between muscle strenght and the level of independence in Activity daily life (ADL) of stroke patients with an upper etremity r value of 0.901 and a lower extremity r value of 0.881, the r value obtained a positive correlation. It is hopes that the results of this reseach will be developed by future reseachers into qualitative reseach related to muscle strength and the level of independence in activity dailiy life (ADL) in stroke patients.